Item analysis of the role of teachers in efforts to prevent the three great sins of education with rasch modeling - Andrian, Muhammad; Martodiryo, Suratno; Rahmattullah, Muhammad; Hasanah, Mahmudah (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study aims to test reliability and validity, namely finding statement items that can be measured precisely as well as finding statement items that can be submitted as material to measure the instrument of the teacher's role in cultivating student character values in efforts to prevent the three deadly sins in education. The Three deadly sins in education, based on this version, are intolerance, sexual violence, and harassment or bullying. The sample of 197 people was taken based on the Isaac and Michael formula with a sampling error rate of 5% selected using a systematic sampling technique from 613 people. The instrument was prepared, revised and validated using the Rasch model. The results showed that the separation of 15.26 items could identify the respondents. The reliability value of the item is 0.83, which is categorized as good. Cronbach's alpha value is 0.80, indicating that the value is excellent and consistent. Instrument difficulty is classified as complicated, complex, medium, and accessible. The instrument of efforts to prevent three deadly sins in education is declared reliable and valid with the criterion of "good", and 12 of the 15 points of the statement are said to be "valid", so to test the role of teachers in cultivating student character values can be measured using this instrument. So, it can be concluded that the instrument is qualified and can be used as material to measure the role of teachers in cultivating student character values in schools.